The effect of firms' partial retirement policies on the labour market outcomes of their employees - Conny Wunsch; Martin Huber; Michael Lechner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper, we assess the impact of firms introducing part-time work schemes for gradual labour market exit of elderly workers on their employees labour market outcomes. The analysis is based on unique linked employer-employee data that combine high-quality survey and administrative data. Our results suggest that partial or gradual retirement options offered by firms are an important tool to alleviate the negative effects of low labour market attachment of elderly workers in ageing societies.
Keywords: J14; J26; C21; 330